Investigating the use of concrete and RCC instead of HMA in highway pavement in hot regions - Sedat Özcanana; Turan Fıratb; Özgür Özcana (Građevinar, 2024)
This study examines the impact of temperature on the Cizre-Silopi highway’s bituminous hot mix asphalt (HMA) pavement, focusing on rutting issues exacerbated by high temperatures, which can reach up to 50 °C in the region. Despite rapid deterioration, especially under heavy truck traffic, the HMA pavement exhibited significant stability and flow resistance loss (approximately 52 %) between 20 and 50 °C. Concrete (C25) and roller-compacted concrete (RCC) pavements displayed minimal strength reductions under the same temperature conditions. These findings suggest that given the prevalent high temperatures and heavy axle loads in the region, concrete (C25) or RCC should be prioritised over HMA for pavement construction to enhance resistance against wheel rutting and temperature-induced damage. The observed rutting issues, even in the initial summer post-construction, underscore the urgency of adopting more temperature-resistant materials for road infrastructure under specified climatic conditions.